Contaminants of emerging concern in freshwater fish from four Spanish Rivers - Pico, Y.; Belenguer, V.; Corcellas, C.; Diaz-Cruz, M. S.; Eljarrat, E.; Farré, M.; Gago-Ferrero, P.; Huerta, B.; Navarro-Ortega, A.; Petrovic, M.; Rodríguez-Mozaz, S.; Sabater, L.; et al. (Science of The Total Environment, 2019)
This study investigated the occurrence of 135 contaminants of emerging concern (CECs) – pharmaceuticals, pesticides, a set of endocrine disrupting compounds (EDCs) (parabens, bisphenols, hormones, triazoles, organophosphorus flame retardants and triclosan), UV-filters, perfluoroalkyl substances (PFASs) and halogenated flame retardants (HFRs) – in 59 fish samples, collected in 2010 in 4 Spanish Rivers (Guadalquivir, Júcar, Ebro and Llobregat). Of the 135 CECs, 76 including 8 pharmaceuticals, 25 pesticides, 10 EDCs, 5 UV-filters, 15 PFASs and 13 HFRs were detected. Pharmaceuticals were the less frequently found and at lower concentrations. Pesticides, EDCs, UV-filters, PFASs and HFRs were detected more frequently (>50% of the samples). The maximum concentrations were 15 ng/g dry weight (dw) for pharmaceuticals (diclofenac), 840 ng/g dw for pesticides (chlorpyrifos), 224 ng/g dw for EDCs (bisphenol A), 242 ng/g dw for UV-filters (EHMC), 1738 ng/g dw for PFASs (PFHxA) and 64 ng/g dw for HFRs (Dec 602). The contaminants detected in fish are commonly detected also in sediments. In light of current knowledge, the risk assessment revealed that there was no risk for humans related to the exposure to CECs via freshwater fish consumption. However, results provide detailed information on the mixtures of CECs accumulated that would be very useful to identify their effects on aquatic biota.
Keywords: Accumulation; Aquatic organisms; Co-occurrence of contaminants; Fish consumption; Risk assessment; River quality; dept.che